For Children - Eyzaguirre, Rómulo (1921)
It is a conviction of all that, at the high number of deaths from tuberculosis, which affects our numeral settler, weighs about him other coefficient, which represents the infant mortality rate, has a numerical value which equates to tuberculosis, and has the aggravating circumstance at this time relate on capital income life. It is true that all high birth city like ours, also has a high mortality, but this statement never explain, in Lima, the mortality of which are still within the first year of life, grow up to 7.77 per thousand inhabitants, rate at which it exceeded that found in other capital cities, and only resembles our own figure of fatality from tuberculosis, a figure already known to all, and makes our capital, of most tuberculous cities.